2003
DOI: 10.1139/h03-029
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Anthropometric, Physiological, and Skill-Related Tests for Talent Identification in Female Field Hockey

Abstract: The purpose of the present study was to develop an effective testing battery for female field hockey by using anthropometric, physiological, and skill-related tests to distinguish between regional representative (Rep, n = 35) and local club level (Club, n = 39) female field hockey players. Rep players were significantly leaner and recorded faster times for the 10-m and 40-m sprints as well as the Illinois Agility Run (with and without dribbling a hockey ball). Rep players also had greater aerobic and lower bod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
64
0
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(75 citation statements)
references
References 9 publications
5
64
0
6
Order By: Relevance
“…It was reported that a battery of anthropometric and morphological tests could distinguish between players of different ability in the same sport (Keogh, 2003). The same was true for the field hockey (Scott, 1991;Manna et al, 2009;Singh et al, 2010).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…It was reported that a battery of anthropometric and morphological tests could distinguish between players of different ability in the same sport (Keogh, 2003). The same was true for the field hockey (Scott, 1991;Manna et al, 2009;Singh et al, 2010).…”
Section: Discussionmentioning
confidence: 91%
“…Estimation of back strength of Indian inter-university male hockey players and significant positive correlations of back strength with height, weight, BMI, hip circumference, % lean body mass and abdominal muscle endurance was reported . Evaluation of anthropometric, physiological and skillrelated tests for talent identification in female field hockey was also reported (Keogh et al, 2003). Correlations of anthropometric characteristics and physical fitness tests remained less reported, especially in Indian context.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, body fat percentage measurement is an important anthropometric marker often assessed in sport conditioning programs. Keogh et al [15] evaluated the association between anthropometric variables and performance in physical fitness tests comparing recreational athletes to elite athletes. Greater values in the vertical jump test, multistage fitness test, and 10 m and 40 m speed tests were observed in subjects with the lowest percentage of fat (elite group).…”
Section: Discussionmentioning
confidence: 99%
“…Correlations between these variables and sports performance are widely related in the scientific literature in several sports [9,14,15,29,30,34].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation